A Topical Anesthetic and Lidocaine Mixture for Pain Relief During Keloid Treatment: A Double-Blind, Randomized Controlled Trial. Issue 1 (January 2017) - Usanakornkul, Arnik; Burusapat, Chairat
Abstract : BACKGROUND: Keloids are abnormal overgrowth of collagen fibers, and the first-line treatment includes intralesional injection of triamcinolone acetonide (TA), which is associated with pain. OBJECTIVE: To study the benefit of applying topical anesthetics or a 1:1 mixture of 1% lidocaine and TA at the TA injection site to alleviate pain during keloid treatment. METHODS AND MATERIALS: A double-blind, randomized controlled trial was conducted. Four TA injection methods were tested: control, lidocaine, topical, and combined. A visual analog scale (VAS) was used to assess needle-stick and injection pain. Data on pain duration after injection were also collected. RESULTS: Forty patients were enrolled (mean age, 37.1 years). The VAS scores of needle-stick pain in the control, lidocaine, topical, and combined groups were 4.18 ± 2.12, 3.82 ± 2.48, 2.03 ± 2.02, and 2.20 ± 1.99, respectively. Pain statistically decreased in the topical and combined groups. Intralesional injection pain (VAS) scores in the control, lidocaine, topical, and combined groups were similar as follows: 4.97 ± 2.50, 4.97 ± 2.79, 4.10 ± 2.80, and 4.43 ± 2.68, respectively. CONCLUSION: Application of topical anesthetics significantly relieved needle-stick pain, especially at sternum and auricular keloids; administration of a lidocaine mixture did not alleviate pain during injection.